The Influence of Parenting Styles on the Development of Self-Regulation in Adolescents - Siti Fathimah Azzalathifa; Luluk Indri Sofia; Najwa Layda Rahma; Meyla Zahwa Aulia Saputra; Ummi Masrufah Maulidiyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Self-regulation represents a critical developmental milestone during adolescence, significantly influencing academic achievement, social relationships, and long-term well-being. This literature review examines the relationship between parenting styles and self-regulation development in adolescents, synthesizing recent empirical evidence from 2023-2025. Drawing from Baumrind's parenting style framework and contemporary self-regulation theories, this review analyzes how authoritative, authoritarian, permissive, and neglectful parenting approaches differentially impact adolescents' capacity for emotional regulation, behavioral control, and cognitive self-management. Findings indicate that authoritative parenting, characterized by warmth combined with appropriate autonomy support, consistently predicts superior self-regulation outcomes. Conversely, authoritarian and neglectful parenting styles correlate with deficits in emotional regulation and increased behavioral problems. The review highlights emotion regulation strategies as critical mediating mechanisms and discusses implications for educational interventions and family-based programs within global education frameworks. This synthesis contributes to understanding how culturally-sensitive, evidence-based parenting practices can promote optimal self-regulation development in diverse adolescent populations.